KONFLIK KERJA DALAM ORGANISASI: IMPLIKASINYA TERHADAP PRESTASI KERJA KARYAWAN (Studi pada Karyawan Pemasaran PT. Krida Dinamik Autonusa Mataram) - Cahyadi, Irwan; Anggriani, Rini; Imbayani, I Gusti Ayu; Puspitawati, Ni Made Dwi (Distribusi - Journal of Management and Business, 2026)
In organizational practice, interaction between employees is unavoidable because work is generally done in teams or across departments. Differences in educational background, experience, character, values, and interests often trigger the emergence of work conflicts. This study was conducted to analyze the influence of factors causing employee conflict consisting of resource competition, individual characteristics, task dependency, communication barriers, job boundary blurring, and status issues on the work performance of marketing employees at PT. Krida Dinamik Autonusa Mataram. Data were collected by distributing questionnaires to 54 respondents, then the collected data were analyzed using multiple linear regression analysis methods, by conducting a t-test to prove the proposed hypothesis. The results of the study showed that there was a negative and significant influence between factors causing employee conflict consisting of resource competition, individual characteristics, communication barriers, job boundary blurring, and status issues on the work performance of employees at PT. Krida Dinamik Autonusa Mataram, while the task dependency variable did not have a significant influence on work performance. Companies are advised to improve fair and effective resource management to reduce competition among employees and strengthen working relationships through interpersonal communication and teamwork training. Furthermore, internal communication systems need to be improved to be more opens and clear, and job descriptions should be structured to avoid overlapping tasks. Management also needs to create a transparent system for assigning status and positions to minimize conflict, and develop effective conflict management mechanisms through internal mediation and improving leadership skills in handling workplace conflicts.